Corrosion protection application of liquid-infused surface with self-healing via regional growth of layered double hydroxide films on aluminum alloy - Jiang, Shuyue; Zhang, Haifeng; Song, Keguan; Liu, Xiaowei (Colloids and surfaces. A, Physicochemical and engineering aspects, 2021)
[Display omitted] Corrosion of aluminum and its alloys in marine system severely restricts their development and application. Therefore, the development of anti-corrosion ability of aluminum and its alloys is a subject of great importance. In this work, the liquid-infused surface (denoted as sample LR) with self-healing property is proposed. The porous structure prepared by laser ablation can store the lubricant oil. The regional growth of layered double hydroxide (LDH) films can lock in place the lubricant oil. Lubricant film is the key to self-healing ability of sample LR. The anti-corrosion and self-healing properties of sample LR were evaluated by electrochemical tests after immersed in 3.5 wt.% NaCl for different time. For the anti-corrosion ability, the corrosion current density of sample LR is 0.02 μA/cm2 after immersed for 48 h, which is ca.1 orders of magnitude lower than that of untreated AA1060 alloy (0.25 μA/ cm2). Correspondingly, the low-frequency impedance modulus of sample LR is 318 kΩ⋅ cm2, which is bigger than AA 1060 alloy (3.3 kΩ⋅cm2). For the self-healing property, low-frequency impedance modulus of sample LR immersed for 1 day (358 kΩ· cm2) is basically equal to that of sample LR immersed for 9 days (349 kΩ·cm2). Therefore, the fabricated sample LR shows the outstanding anti-corrosion and self-healing ability thus it has a widespread application prospect in industry.